2018
DOI: 10.1002/ccd.27551
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the planned one‐ and elective two‐stent techniques in patients with coronary bifurcation lesions with or without acute coronary syndrome from the COBIS II Registry

Abstract: Planned one-stenting reduced TLF in patients with ACS and it also might be beneficial in those without ACS for the treatment of coronary bifurcation lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Acute coronary syndrome is a stage where coronary plaques become unstable ( 25 ). The COBIS Registry showed a lower rate of 3-year TLF after the PS approach for patients with ACS but no difference between the PS and upfront 2-stent for patients without ACS ( 26 ), confirmed by another study of Korean team which further found that SB lesion length was an independent factor of TLF ( 27 ). The underlying mechanisms for a higher rate of TLF in patients with ACS were multifactorial, of them DAPT might be one major reason ( 25 ).…”
Section: Discussionmentioning
confidence: 76%
“…Acute coronary syndrome is a stage where coronary plaques become unstable ( 25 ). The COBIS Registry showed a lower rate of 3-year TLF after the PS approach for patients with ACS but no difference between the PS and upfront 2-stent for patients without ACS ( 26 ), confirmed by another study of Korean team which further found that SB lesion length was an independent factor of TLF ( 27 ). The underlying mechanisms for a higher rate of TLF in patients with ACS were multifactorial, of them DAPT might be one major reason ( 25 ).…”
Section: Discussionmentioning
confidence: 76%
“…Implantation of no more than one stent was observed in 70% of patients, although patients with multi-vessel disease represented almost two-thirds of the analyzed group. Such an approach in which a lower number of stents is preferred may be one of the reasons why satisfactory outcomes were achieved in those patients, as the reduced range and complexity of the intervention decreased the risk of complications [16,17] consideration of paramount importance in the vulnerable elderly population. However, the combined length of stents per procedure was relatively long, mean fluoroscopy exposure was elevated, and mean contrast volume was high, which suggests that although a relatively low number of stents were implanted per procedure, those procedures remained difficult, time-consuming and laborious [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…It showed that adverse cardiac events were significantly more common with the two-stent technique than the provisional technique in patients with ACS, as opposed to the patients without ACS. Although it should be taken into consideration that this was not a randomized study and that lesions treated with the implantation of two stents had a higher prevalence of more complex lesions, true bifurcations, left main stem (LMS) lesions as well as multivessel disease [7].…”
Section: Discussionmentioning
confidence: 99%